2016
DOI: 10.1088/0964-1726/25/9/095055
|View full text |Cite
|
Sign up to set email alerts
|

Development and field application of a nonlinear ultrasonic modulation technique for fatigue crack detection without reference data from an intact condition

Abstract: In this study, a fatigue crack detection technique, which detects a fatigue crack without relying on any reference data obtained from the intact condition of a target structure, is developed using nonlinear ultrasonic modulation and applied to a real bridge structure. Using two wafer-type lead zirconate titanate (PZT) transducers, ultrasonic excitations at two distinctive frequencies are applied to a target inspection spot and the corresponding ultrasonic response is measured by another PZT transducer. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Among them, the ultrasonic guided wave method has been recognized as one of the efficient nondestructive testing (NDT) approaches to scan long structural members. It has been applied to inspect pipelines, 22,23 cables, 24,25 rails, 26–28 and many other types of structures 29–31 . One of the common NDT strategies using guided waves is called the pulse‐echo method, where the transducer simultaneously works as the actuator and sensor 32 …”
Section: Introductionmentioning
confidence: 99%
“…Among them, the ultrasonic guided wave method has been recognized as one of the efficient nondestructive testing (NDT) approaches to scan long structural members. It has been applied to inspect pipelines, 22,23 cables, 24,25 rails, 26–28 and many other types of structures 29–31 . One of the common NDT strategies using guided waves is called the pulse‐echo method, where the transducer simultaneously works as the actuator and sensor 32 …”
Section: Introductionmentioning
confidence: 99%
“…There have also been studies that have introduced a nonlinearity index (NI) and used this for crack detection. Lim et al [ 25 ] conducted a non-destructive test with the sign of two factors: the skewness and the median of the NI distribution. Li et al observed the correlation between the acoustic nonlinearity parameter of the stainless steel plate and the thermal-induced degradation using a phase reversal approach [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the VAM approach (Lim et al, 2016;Liu et al, 2016;Zagrai et al, 2004) employs two excitation sources to generate different frequencies, namely a lowfrequency (LF) pumping wave and a high-frequency (HF) probing wave. When these two excitations are mixed and applied to the structure under detection, they will interact with a rough contact interface (Jhang, 2009).…”
Section: Introductionmentioning
confidence: 99%